2017
DOI: 10.1371/journal.pcbi.1005822
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying influential neighbors in animal flocking

Abstract: Schools of fish and flocks of birds can move together in synchrony and decide on new directions of movement in a seamless way. This is possible because group members constantly share directional information with their neighbors. Although detecting the directionality of other group members is known to be important to maintain cohesion, it is not clear how many neighbors each individual can simultaneously track and pay attention to, and what the spatial distribution of these influential neighbors is. Here, we ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 42 publications
2
75
0
Order By: Relevance
“…The linear propagation of information in all group sizes suggests that there is no amplification of the individual tendency to perform a U-turn: the time between two successive individuals performing U-turns does not decrease with the number of fish that already performed a U-turn. This suggests that individuals only pay attention to a small number of neighbours at a given time as was shown in [18].…”
Section: Spatiotemporal Dynamics Of Collective U-turnmentioning
confidence: 86%
See 1 more Smart Citation
“…The linear propagation of information in all group sizes suggests that there is no amplification of the individual tendency to perform a U-turn: the time between two successive individuals performing U-turns does not decrease with the number of fish that already performed a U-turn. This suggests that individuals only pay attention to a small number of neighbours at a given time as was shown in [18].…”
Section: Spatiotemporal Dynamics Of Collective U-turnmentioning
confidence: 86%
“…show that the interval between successive turns of individuals during a collective U-turn decreases with swimming speed, although distance between individuals may also play a role [19]. However, the mean time interval between successive individual U-turns is almost constant and independent of the group size, once time has been rescaled by the group velocity.…”
Section: /11mentioning
confidence: 93%
“…Despite the fact that the design of the experiments involved a constrained environment for the fish, i.e., a circular corridor, in order to obtain a clear collective response, these results can be extended in further studies in more complex environments, involving societies composed of more agents, in order to study in more detail how information propagates between the agents such as shown in Jiang et al (2017), how the robots can accurately modulate the behaviors of the fish, and, possibly, how the robots can automatically adapt to these behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…1). This is a common setup to study the collective behavior of fish (Abaid and Porfiri 2010;Jiang et al 2017) and offers a binary choice for the fish, as they can either move in a clockwise direction (CW) or a counterclockwise (CCW), which will be used to evaluate the effect of the robots on the collective decisions of the fish. The dimensions of the corridor were as follows: an external diameter of 58 cm, an internal diameter of 38 cm, and a corridor's width of 10 cm.…”
Section: Arenamentioning
confidence: 99%
“…Such social structures may in fact be common in nature, where visual occlusion [30,31] or other mechanisms generate clustering in animal groups [22]. Furthermore, existing empirical evidence suggests that, for many social animal species, individuals pay attention to their closest 1-7 nearest neighbors [17,18,27,32], resulting in relatively sparse social networks.…”
Section: Spatial Clustering and Sparseness Improves The Filtering Of mentioning
confidence: 99%